PENINGKATAN HASIL BELAJAR SISWA KELAS V MATERI ORGAN PERNAPASAN DAN FUNGSINYA PADA HEWAN DAN MANUSIA MELALUI MODEL TWO STAY TWO STRAY DI SDI KAKEULARAN KABUPATEN MALAKA - Seran, Sabina H.; Koroh, Taty R.; Nawa, Netty E A (Journal of Character and ELementary Education, 2024)
The aim of this research is to determine the improvement in learning outcomes of class V SDI Kakeularan students through the Two Stay Two Stray learning model on the subject of respiratory organs and their functions in animals and humans. This research is a type of classroom action research with implementation stages including planning, implementation, action, observation and reflection. The research subjects were 25 fifth grade elementary school students. The data collection techniques used in this research were observation and tests, and the instruments used were observation sheets and learning outcomes tests. Based on the research results, it can be concluded that student learning outcomes have increased after applying the two stay two stray model to the subject of respiratory organs and their functions in animals and humans. This can be seen in the first cycle student learning results, which showed that students completed their learning with a percentage of 48% with 12 students completing it. Meanwhile, in cycle II, student learning outcomes were completed with a percentage of 84%, with 21 students completing the results. From cycle I to cycle II there was an increase of 36%. In this way, this classroom action research was successful, so that the researchers stated that the application of the Two Stay Two Stray learning model could improve student learning outcomes on the subject of respiratory organs and their functions in animals and humans.